Exploring Trends in EFL Students Theses from 2014 to 2018 - Muhammad Affan Ramadhana; Fatima Fatima (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2021)
This study aims to explore the themes and methods most often applied by EFL students in their thesis. Sampling is done randomly by collecting theses submitted by students from five consecutive years (2014 – 2018). The data obtained is entered into several tables and graphs, followed by several descriptions of the values contained in the table or graph. This research shows the increase and decrease of student interest regarding the selection of themes and methods they used in their theses. The most widely used theme is vocabulary, and the most frequently used research method is pre-experimental.